Violence Against Healthcare Workers at Primary Care Centers in Dammam and Al Khobar, Eastern Province, Saudi Arabia, 2019 - Alsmael MM; Gorab AH; AlQahtani AM (International Journal of General Medicine, 2020)
Mustafa M Alsmael,1 Ali H Gorab,1 Areej M AlQahtani2 1Family Medicine Academy, First Health Cluster, Ministry of Health, Dammam, Saudi Arabia; 2First Health Cluster, Ministry of Health, Al Khobar, Saudi ArabiaCorrespondence: Ali H Gorab PO Box 1162, Al Khobar 31952, Kingdom of Saudi ArabiaTel +966 50 680 6538Fax +966 13 891 1159Email Ghorabah@gmail.comPurpose: Workplace violence is common throughout the world. It causes many serious problems in the healthcare sector, where it significantly impacts healthcare workers, the services provided, and organizations as a whole. However, few studies have investigated these issues in Saudi Arabia. This study examined the prevalence of violence against healthcare workers at primary care centers in Dammam and Al Khobar, in the Eastern Province of Saudi Arabia. The study also assessed the types, perpetrators, perceived causes, and consequences related to such violence. Here, the aim was to understand how healthcare workers responded to violence and gauge their awareness of a reporting system.Patients and Methods: A total of 360 healthcare workers (180 each from primary care centers in Dammam and Al Khobar) were invited to complete structured, self-administered questionnaires. As such, this study employed a cross-sectional analytical design.Results: The prevalence of workplace violence among all participating health workers was 46.9%, with approximately 90% of these workers reporting verbal violence, 34.3% having been subject to intimidation, and 3% reporting physical violence. Approximately 75% reported that violent events were initiated by patients, while 45.6% reported that the events were initiated by patients’ companions. Healthcare workers’ reactions included reporting events to their supervisors or the police, but 46.7% said they did nothing; the most common reason was perceived inefficacy. Finally, only 36.4% of all participants were aware of a violence reporting system.Conclusion: This study showed that healthcare workers were commonly exposed to different forms of violence, but often either did not react to it or did not report it. Further, there was relatively little awareness of how to manage and report workplace violence, thus indicating the need for healthcare workers to receive relevant education and training. A national program should also be established to track and prevent workplace violence.Keywords: cross-sectional study; exposure to violence, health personnel, primary health care, workplace violence